2023
DOI: 10.3390/buildings13071792
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Foremen’s Influence on the Safety Behavior of Construction Workers Based on Cognitive Theory

Abstract: In this study, a behavioral influence model based on cognitive theory was developed to investigate foremen’s influences on construction workers’ safety behavior. In the model, three foreman behaviors were considered, such as leading by example (LE), safety teaching (ST), and safety monitoring (SM). Five cognitive stages of a worker are also considered in the model, such as situation awareness, safety knowledge, subjective norm, safety attitude, and taking action. To obtain empirical data for the model paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…First, according to the TBM guidelines provided by KOSHA, it is recommended that the TBM should be organized with a team leader at the center, and the ideal team size is 4-10 members. Moreover, Demirkesen and Arditi [33] suggested that active worker participation in communication can reduce incidents and enhance safety awareness. Therefore, based on the analysis results presented in Section 4.1, it can be inferred that the mobile TBMs followed the TBM guidelines set by KOSHA more than the conventional TBMs.…”
Section: Discussionmentioning
confidence: 99%
“…First, according to the TBM guidelines provided by KOSHA, it is recommended that the TBM should be organized with a team leader at the center, and the ideal team size is 4-10 members. Moreover, Demirkesen and Arditi [33] suggested that active worker participation in communication can reduce incidents and enhance safety awareness. Therefore, based on the analysis results presented in Section 4.1, it can be inferred that the mobile TBMs followed the TBM guidelines set by KOSHA more than the conventional TBMs.…”
Section: Discussionmentioning
confidence: 99%
“…In such a fast-paced environment, safety communication within the work crews is essential for ensuring that FCFWs are immediately made aware of hazards and safety information by their crewmates. While safety training and safety-related information from safety managers and the leadership are important [17,18], coworkers who work together are the closest and most stable working unit on the job site. Therefore, safety communication between FCFWs has a significant impact on the prevention of industrial accidents [19].…”
Section: Introductionmentioning
confidence: 99%